G-CSF-mobilized peripheral blood mononuclear cells combined with platelet-rich plasma accelerate restoration of ovarian function in cyclophosphamide-induced POI rats†. Issue 1 (29th April 2019) - Huang, Qiuyan; Liu, Bo; Jiang, Rufang; Liao, Shengbin; Wei, Zhiyao; Bi, Yin; Liu, Xueyuan; Deng, Rong; Jin, Yufu; Tan, Ying; Yang, Yihua; Qin, Aiping
Abstract: Peripheral blood mononuclear cells (PBMCs) are rich in hematopoietic cells and mesenchymal stem cells. Platelet-rich plasma (PRP) is rich in various growth factors. PBMCs and PRP have been suggested, individually, to restore ovarian function by improving the local microenvironment. The current study investigated the effect of granulocyte colony-stimulating factor (G-CSF)-mobilized PBMCs combined with PRP on restoring ovarian function in rats with primary ovarian insufficiency (POI). Thirty adult female rats were randomly subdivided into five groups: normal control (control), cyclophosphamide (CTX) plus subsequent PBS (POI + PBS), CTX plus subsequent PRP (POI + PRP), CTX plus subsequent G-CSF-mobilized PBMCs (POI + PBMCs), and CTX plus subsequent G-CSF-mobilized PBMCs combined with PRP (POI + PBMCs + PRP). CTX exposure induced the typical POI phenotype with increased diestrus; shortened estrus; follicle arrest at all stages; decreased serum levels of estradiol-17β (E2) and anti-Mullerian hormone (AMH); and increased levels of follicle-stimulating hormone (FSH). Transplantation of mobilized PBMCs with PRP resulted in a much earlier restoration of the estrous cycle, sex hormone levels, and preantral follicle growth in POI rats. Expression of the male-specific Sry gene in the ovarian tissues of POI + PBMCs + PRP female recipient rats was evident at 5, 10, and 20 days posttransplantation along with significant increases in the expression of angiogenesis markers CD34 + and VEGF and folliculogenesis markers AMH and FSHR. Additionally, PBMCs in combination with PRP mitigated granulosa cell apoptosis by downregulating BAX and upregulating BCL-2. These results demonstrate that G-CSF-mobilized PBMCs combined with PRP accelerate the restoration of ovarian function in POI rats by increasing ovarian neovascularization, reducing granulosa cell apoptosis, and promoting folliculogenesis. Abstract : G-CSF-mobilized PBMCs combined with PRP improves ovarian function and restores the growth of preantral follicles in CTX-induced POI rats.